Representation of Egyptian Arab Identity in the Film Ayat-Ayat Cinta (2008): A Narrative and Visual Analysis - Fauziyah, Nur Lailatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze how Egyptian Arab identity is represented in the film Ayat-Ayat Cinta (2008). While numerous studies have examined the representation of identity and religiosity in popular films, research specifically analyzing the construction of Egyptian Arab identity through the integration of narrative and visual elements remains limited. The focus of this research is directed at the construction of religious identity, culture, and gender relations as depicted through the film’s narrative and visual components. ​The study employs a descriptive-qualitative method with a documentation study approach, involving intensive observation and viewing of the film. Data analysis was conducted by identifying narrative structures (plot, characters, conflict, dialogue) and visual elements. The data were analyzed using Stuart Hall’s representation theory, which posits that identity is constructed through systems of meaning within the media. In Ayat-Ayat Cinta (2008), Egyptian Arab identity is represented through religious symbols such as Al-Azhar, the use of formal Arabic, and the construction of Arab women. ​The objective of this research is to observe how the meaning of Egyptian Arab identity is built within the media. The results indicate that the film represents Egypt as an ideal religious space and a center of Islamic scholarly authority, while simultaneously constructing the identity of Arab women through symbols of piety and honor. This representation demonstrates that Egyptian Arab identity in the film is not merely a reflection of social reality, but rather a result of narrative and visual framing that shapes a specific image according to the film’s production perspective.